Assessment of Aflatoxin M1 in human breast milk in Rafsanjan, Iran - Somayeh Pourtalebi; Seyyed Amin Ayatollahi Mousavi; Zahra Asadollah; Seyyed Mahdi Mousavi (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: Aflatoxins (AFs) are a group of highly toxic mycotoxins present both in the environment and in foodstuffs. The food of infants should be safe and free of various pollutants, including breast milk mycotoxins. This study aimed to measure the mycotoxin of Aflatoxin M1 (AFM1) in human milk samples obtained from lactating mothers living in Rafsanjan city, Iran.  Materials and Methods: In the current cross-sectional study, breast milk samples were collected from 150 lactating mothers in Rafsanjan city from September 2015 to April 2016 using the structured food-frequency questionnaire. The AFM1 was measured by employing enzyme-linked immunosorbent assay specific kits. The statistical analysis was performed in SPSS software (version 16). Results: The AFM1 was detected in 98 mothers (65%) with a mean concentration of 14.69±8.15 ng/kg, ranging from 5.02 to 41.25 ng/kg. The AFM1 concentration exceeded the tolerable and accepted limit promulgated by the European Union and the USA (25 ng/kg) in only 10 milk samples. Moreover, in 59 milk samples, the AFM1 concentration exceeded the limit recommended by Australia and Switzerland (10 ng/kg). Conclusion: According to the results of the present study, lactating mothers and their infants are at risk of AFM1 exposure in southern Iran. Accordingly, the examination of AFM1 concentrations in lactating mothers, as a critical postnatal exposure marker of infants to this carcinogenic compound, requires further studies in various seasonal periods and different parts of Iran